THE EFFECT OF REGIONAL FINANCIAL MANAGEMENT, REGIONAL FINANCIAL ACCOUNTING SYSTEMS AND INTERNAL CONTROL SYSTEMS GOVERNMENT ON THE REGIONAL GOVERNMENT PERFOMANCE (CASE STUDY ON BKD IN BOYOLALI REGENCY) - Rismawati Rismawati; Indra Lila Kusuma; LMS Kristiyanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Abstract: This study aims to determine the Effect of Regional Financial Management, Regional Financial Accounting System and Internal Control System Government on Regional Government Perfomance. The methodhology used in this research is the quantitative. The population used is all employee of BKD Boyolali. In this study a sample of 54 employees. While for the technique of data collection is done by using questionnaires. To facilitate problem solving, this study was conducted using multiple linear regression models with the help of IBM SPSS Statistics 25. Based on the second partial test, shows that the Regional financial Accounting System variable has a significant effect on on Regional Government Perfomance. Based on the third partial test, shows that the Internal Control System Government variable has a ignificant effect on on Regional Government Perfomance. Based on the results of the simultaneous data test,be concluded that simultaneously or together the variables of the Effect of Regional Financial Management, Regional Financial Accounting System and Internal Control System Government is a factor that effect the Regional Government Perfomance. Keywords: Regional Financial Management, Regional Financial Accounting System and Internal Control System Government, Regional government Perfomance